International Insertion Quality: The European Union (EU-27) Case (European Journal of Marketing and Economics, 2024)
This research has a double aim. On the one hand, to introduce the International Insertion Quality (IIQ) construct. On the other hand, to present a classification of the European Union (EU-27) countries to establish which of them have a better IIQ. For this purpose, first, the IIQ construct is presented. Second, the evolution of the export’s technological intensity degree of the EU-27 countries between the periods 2001-2003 and 2015-2017 is analyzed. Then, the evolution of the exports' diversification degree, both, by products and by destination markets in the same periods, is studied. This allows to observe in perspective the qualitative changes that have taken place between the two reference periods. In addition, a classification matrix of countries according to their quality of insertion in international trade is presented. The results allow arguing that Germany and France are the countries that have a higher IIQ. Also, there are nations that have a high technological content, but moderate markets diversification and/or products concentration; and other countries that have geographical and/or goods diversification, despite the fact that their exports contain a medium-low-level of technological intensity. This research allows concluding which EU-27 countries should work on their commercial policies to encourage the diversification of their exports and/or the development of products with greater technological content.
Keywords: International Insertion Quality (IIQ), export diversification, technological intensity, European Union.